A relação entre letramentos escolares e não escolares na construção de comunidades leitoras via booktubers - Guiomar Timoteo Coura (2020)
This study investigates the process of building reader communities in virtual literary channels, analyzing the relationship between school and non-school literacy practices involved in this process. Our aim was to learn about the social reading practices of students at a public school, characterizing the participation of students in virtual reading communities and the mediation of reading done by booktubers. For this investigation, we opted for a qualitative research carried out with high school students from a state public school in the city of Santa Luzia, Minas Gerais. We initially analyzed the most viewed virtual literary channels on the YouTube platform: TLT, Cabine Literária, Canal da Pam Gonçalves, Nuvem Literária e Ler Antes de Morrer.The virtual literary channels form reader communities called booktube, whose presenters are known as booktubers. The presentation made by the booktubers in the videos is a kind of conversation about the books that is similar to the review genre. The interaction between community participants takes place via the comments tool provided by the YouTube platform, using Web 2.0 technology. The videos are usually produced in rooms decorated by a bookcase, which composes the environment and emits various information, characterizing the booktubers as agents, influencers and mediators of reading. Multimodality appears with the use of sounds, images and written text, as a result of modern technologies. In this sense, the activity of the presenters of these channels registers a literacy practice that occurs outside the school environment. The second moment of data collection took place through the articulation between the application of a questionnaire with open and closed questions answered by 67 students and semi-structured interviews conducted with students who considered themselves readers and knowledgeable of the virtual literary channels. The questionnaire data revealed that the romance genre is the most read by students and that the choice of books is based mainly on tips from friends and the influence of the media. On the other hand, the taste for reading still continues to be aroused, mostly, by parents and guardians. Reading is part of the conversation of adolescents and young subjects in this research, and most of them consider reading as a pleasant activity. Almost all students interviewed consider themselves to be readers, but few read books recommended by teachers. As for reading practices that take place outside of school, we realize that students know and participate in reading clubs or book clubs in person or online, from which they receive and accept reading recommendations. The data from the group interviews show that students read and buy books due to the influence of reviews made on virtual literary channels. The discursive strategies used by the presenters are what generate adherence to reading, in addition to the continuity of reading and the reading proposals made by the channels that motivate users. Students prefer reading printed books to reading virtual books and movies. These data reveal that students’ social reading practices are influenced by school literacies, as students read from what is taught by the school, but there are also other literacy practices that influence students’ reading, but which tend not to be recognized or legitimized by the school institution.